Modelowanie cen energii elektrycznej na giełdach energii w wybranych państwach Unii Europejskiej - Włodarczyk, Aneta; Zawada, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
There are observable periods of great power price fluctuations in the power market, which arise due to the character of the, product, i.e. electric energy (the inability to store power, the influence of weather conditions, days of the week, time of the day and seasons on demand for power). The authors verified the usefulness of models with the conditional expected value and the conditional variance to describe the properties of rates of return series of power prices coming from three European power exchanges: Polish, Spanish and German. The parameters of the ARX-EGARCH and ARX-ATGARCH models were estimated in relation to logarithmic rates of return of electric energy prices, in which exchange turnover functioned as the exogenic variable. Then, using various comparative criteria, the best models in a given category were pointed out. The above models may be used to analyze the current as well as the future situation on power exchanges, especially in the context of the analysis of market risk that accompanies electric energy purchase and sales transactions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 507-516